SUCCESSFUL ENUCLEATION OF RETROPERITONEAL CYST - Singal, Rikki; Gupta, Samita; Singh, Bir (Journal of Ayub Medical College Abbottabad, 2012)
Retroperitoneal mesenteric cyst is a rare entity among the other mesenteric cysts and intra-abdominal tumours. A 42-year-old woman reported with pain abdomen off and on since one month. There were no other complaints. On ultrasonography a mesenteric cyst was diagnosed. Surgery was planned which revealed a retroperitoneal mesenteric cyst. Enucleation of the cyst was done. In follow-up of 6 months patient is asymptomatic. We are reporting a rarely reported retroperitoneal mesenteric cyst in the mesentery of the descending colon or sigmoid. Keywords: intra-abdominal, colon, retroperitoneal cyst, enucleation, management